Halal Tourism Hospitality: Comparing Standards of Muslim-Friendly Accommodation in Indonesia and Malaysia - Fauzia Ulirrahmi; Umi Rohmah; Betty Eliya Rokhmah (Journal of Social Transformation and Regional Development, 2024)
This study explores the standards of Muslim-friendly accommodations in Indonesia and Malaysia, two countries recognized as leading halal tourism destinations. The primary focus of this research is to identify the differences in the implementation of hospitality standards between the two nations. The findings reveal that Malaysia’s MS 2610:2015 provides a structured and clear framework that governs various aspects of accommodation services in alignment with Islamic principles. In contrast, Indonesia relies on non-binding fatwas issued by the Indonesian Ulema Council (MUI), which, while encompassing a broader scope, lacks the enforcement mechanisms necessary to ensure uniformity within the tourism sector. The flexibility of the MUI fatwa allows for adaptation to local contexts but may lead to uncertainty in execution, especially given Indonesia’s diverse cultural landscape. Although both standards aim to enhance the halal tourism experience, their differing approaches reflect not only the varying levels of regulatory formalism but also the distinct cultural and social contexts of each country.